2003
DOI: 10.1016/s1097-2765(03)00091-1
|View full text |Cite
|
Sign up to set email alerts
|

The Paf1 Complex Is Required for Histone H3 Methylation by COMPASS and Dot1p: Linking Transcriptional Elongation to Histone Methylation

Abstract: Methylation of histone proteins is one of their many modifications that affect chromatin structure and regulate gene expression. Methylation of histone H3 on lysines 4 and 79, catalyzed by the Set1-containing complex COMPASS and Dot1p, respectively, is required for silencing of expression of genes located near chromosome telomeres in yeast. We report that the Paf1 protein complex, which is associated with the elongating RNA polymerase II, is required for methylation of lysines 4 and 79 of histone H3 and for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
678
3
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 666 publications
(733 citation statements)
references
References 45 publications
38
678
3
10
Order By: Relevance
“…It was initially demonstrated in yeast that COMPASS and H3K4 methylation are localized to punctuate sites near the transcription start sites for actively transcribed genes [32,33]. This H3K4 localization pattern also holds true in higher eukaryotic organisms including mammals [34].…”
Section: H3k4 Methylation Distribution Pattern Throughout the Genomementioning
confidence: 92%
See 1 more Smart Citation
“…It was initially demonstrated in yeast that COMPASS and H3K4 methylation are localized to punctuate sites near the transcription start sites for actively transcribed genes [32,33]. This H3K4 localization pattern also holds true in higher eukaryotic organisms including mammals [34].…”
Section: H3k4 Methylation Distribution Pattern Throughout the Genomementioning
confidence: 92%
“…The methyltransferase function of MLLs in human are non-redundant as deletion of either MLLs result in embryonic lethality. Previous studies demonstrated that COMPASS interacts with the elongating form of Pol II via its interaction with the Paf1 complex [32,43]. Therefore, (A) in the absence of H2B monoubiquitination, COMPASS can still interact with the transcribing Pol II via the Paf1 complex and monomethylate H3K4.…”
Section: Figure 2 Subunit Composition For Compass In Yeast and Its Hmentioning
confidence: 98%
“…Therefore, yPAF was postulated to be involved in both RNA polymerase IImediated transcription initiation and elongation. Recently, the yPAF complex has been shown to be required for Rad6-mediated histone H2B-K123 monoubiquitination (Ng et al 2003b;Wood et al 2003), Set1-mediated histone H3-K4 methylation (Krogan et al 2003;Ng et al 2003a), and Dot1-mediated histone H3-K79 methylation (Krogan et al 2003), placing PAF at the center of cotranscriptional histone modifications (for review, see Hampsey and Reinberg 2003). PAF subunits are also required for maintaining proper poly(A) tail length in yeast, suggesting a post-transcriptional role for PAF complex in mRNA processing and maturation (Mueller et al 2004).…”
mentioning
confidence: 99%
“…Several important predictions arising from this E-MAP for novel gene functions have recently been studied and confirmed (10)(11)(12)(13)(14)(15)(16)(17). One such prediction was a connection between SET2, a histone methyltransferase, and Rpd3C(S), a histone deacetylation complex that contains the chromodomain protein Eaf3p as well as Rco1p.…”
Section: Introductionmentioning
confidence: 76%